If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x2+3=52
We move all terms to the left:
x2+3-(52)=0
We add all the numbers together, and all the variables
x^2-49=0
a = 1; b = 0; c = -49;
Δ = b2-4ac
Δ = 02-4·1·(-49)
Δ = 196
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:x_{1}=\frac{-b-\sqrt{\Delta}}{2a}x_{2}=\frac{-b+\sqrt{\Delta}}{2a}\sqrt{\Delta}=\sqrt{196}=14x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-14}{2*1}=\frac{-14}{2} =-7x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+14}{2*1}=\frac{14}{2} =7
| 5x–x–8=20–30+2x | | 3x+9=-3x+-9 | | 102-3n=3 | | G(-3)+13=x-4x | | 0.6-a=1.6 | | 5X-3(3x+4)=5 | | 5-4x+2=-17 | | 4(x-2)=2x+3(x-5) | | 8(1-3x)=-88 | | 3x-12=6x+5 | | -7y+8=41y-2 | | 10b=4(2+5)-6 | | 4x+49=6x+3 | | 2x−8(2x−5)=-2+7(-2x+6) | | (6+6)6=-22x+2 | | 4(2k-10)=8k-40 | | 7x-2(5-x)=15 | | 6y9=3(2y+3) | | 2k-(-20k)+16k-13k-5k=-20 | | (11x-12)+(2x+10)=0 | | 6(5x-6)=-6(4x+6)-5x | | 7(y-7)=2(13+y | | 5x+2(x+4=15 | | 3x+1.2=16 | | 1/4x+4=3x-7 | | 2/3x(x+9)=x+5 | | 8(2+3x)+3(x-3)=-20 | | 10(x)=4^(x-6)+30 | | 17/14=10/7v+1+11/4 | | (x+1)/(2x-1)+(x-1)/(2x+1)=(1)/(2) | | 6(5v-4)=-24+v | | 4m=50 |